The Effect of Jigsaw Type Cooperative Learning Model Assisted By Mind Mapping Media and Environmental Vocabulary Mastery on Narrative Text Writing Skills of Class IX SMP Negeri 2 Batang Anai Students - Maulana, Rafi; Yenni Hayati (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
The purpose of this study was to describe the effect of the jigsaw type cooperative learning model assisted by mind mapping media on short story writing skills, the effect of the Jigsaw type cooperative learning model on short story writing skills of students who have high and low environmental vocabulary mastery. This type of research is quantitative research with experimental method. The research design used is nonequivalent control group design. The population of this study were ninth grade students of SMP Negeri 2 Batang Anai in the 2024/2025 school year. The instruments of this research are objective tests of environmental vocabulary mastery and performance tests of short story text writing skills. Based on the data analysis and discussion above, it can be concluded as follows. First, there is a difference in the results of the performance test of short story writing skills of grade IX students of SMP Negeri 2 Batang Anai using the jigsaw model assisted by mind mapping media with an average of 80.24 and the results of the performance test of short story writing skills using the conventional model with an average of 64.05. Second, there is a difference in the results of the short story writing skills performance test of grade IX students of SMP Negeri 2 Batang Anai with high environmental vocabulary mastery using the jigsaw model assisted by mind mapping media which obtained an average of 88.89 very good qualification (BS) with the results of the short story writing skills performance test of students with high environmental vocabulary mastery using the conventional model which obtained an average of 69.63 more than sufficient qualification (LdC) Third, there is a difference in the results of the short story writing skills performance test of grade IX students of SMP Negeri 2 Batang Anai with low environmental vocabulary mastery using the jigsaw model assisted by mind mapping media which obtained an average of 79.26 good qualification (B) with the results of the short story writing skills performance test of students with low environmental vocabulary mastery using the conventional model which obtained an average of 57.04.